AN ANALYSIS OF JUDICIAL DECISIONS ON GENDER QUOTA FRAUD IN THE CASES OF TACAIMBÓ/PE AND LAJEDO/PE - Siqueira, Cleryston Pessoa de; Arruda Neto, Antonio Justino de; Salles, Eduardo Baldissera Carvalho (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
The present study analyzes gender quota fraud in proportional elections in the municipalities of Tacaimbó and Lajedo, in Pernambuco, Brazil. The study investigates the ways in which female participation is manipulated to formally comply with quotas without ensuring effective representation. The theoretical framework is grounded in the analysis of judicial decisions and the provisions of Article 10, §3 of Law 9.504/97. The research problem is formulated as follows: “To what extent do the cases of Tacaimbó and Lajedo demonstrate a jurisprudence of addressing gender quota fraud?” The general objective is to examine the relevance of judicial decisions in curbing fraud and consolidating the gender quota as an effective mechanism of political inclusion. The specific objectives are: (1) to identify the motivations that led to the annulment of candidacies due to gender quota fraud; (2) to understand the legal decisions addressing gender quota fraud; and (3) to discuss these decisions in conjunction with TSE Resolution 23.735/24 as a mechanism for democratic protection. This study is an applied research project with a descriptive and bibliographic character, adopting a qualitative approach. It employs a comparative content analysis to enable a deeper understanding of the research topic. Data collection was conducted through the analysis of documents, laws, resolutions issued by the Superior Electoral Court (TSE), judicial decisions from the Regional Electoral Court of Pernambuco (TRE/PE) and the TSE, as well as relevant books and updated articles. The chosen method for data analysis and interpretation is content analysis. The analysis of the judicial decisions reveals two primary findings in the fields of politics and law: (1) a negative aspect, highlighting that despite normative frameworks promoting women’s political participation, fraud persists through various means; and (2) a positive aspect, indicating that judicial decisions serve as a reaffirmation of women’s political participation and as an expression of political resistance.
Keywords: Gender Quota; Electoral Law; Fraud; Resistance